2012
DOI: 10.1111/j.1749-6632.2012.06511.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and metabolic syndrome

Abstract: Increasing evidence indicates that several mechanisms, associated or not with antioxidant actions, are involved in the effects of flavonoids on health. Flavonoid-rich beverages, foods, and extracts, as well as pure flavonoids are studied for the prevention and/or amelioration of metabolic syndrome (MS) and MS-associated diseases. We summarize evidence linking flavonoid consumption with the risk factors defining MS: obesity, hypertriglyceridemia, hypercholesterolemia, hypertension, and insulin resistance. Never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 77 publications
(158 reference statements)
1
86
0
2
Order By: Relevance
“…In fact, BMI, WC, and plasma leptin were correlated with energy intake but not with urinary flavanones. To the best of our knowledge, there is no evidence that associates weight loss with flavanones (45). However, the subjects in our study showed a significant decrease in DBP and SBP after both of the 12-wk interventions, as previously reported (30).…”
Section: Discussionsupporting
confidence: 80%
“…In fact, BMI, WC, and plasma leptin were correlated with energy intake but not with urinary flavanones. To the best of our knowledge, there is no evidence that associates weight loss with flavanones (45). However, the subjects in our study showed a significant decrease in DBP and SBP after both of the 12-wk interventions, as previously reported (30).…”
Section: Discussionsupporting
confidence: 80%
“…Epidemiological studies have shown that high intake of diets rich in flavonoids can prevent many chronic diseases including cardiovascular disease, metabolic disease, allergy, and cancer [9], [47][50]. A variety of mechanisms have been proposed by which flavonoids prevent and attenuate inflammatory responses and serve as possible cardioprotective, neuroprotective and chemopreventive agents [8], [9], [11], [47], [48], [51][53]. Apigenin has been reported as an important dietary flavonoid with strong chemopreventive and anti-inflammatory activities [13][19].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids may inhibit the vascular diseases' development through alteration in endothelial cell eicosanoid production [30]. Flavonoids also showed blood pressure lowering effect in hypertensive and normotensive subjects while flavonoids may have beneficial actions in obesity due to their capacity to regulate fatty oxidation and improve adipocyte functionality [31]. Besides, food derived flavonols (quercetin, kaempferol, and myricetin) have been reported to exhibit various biological functions and medicinal properties such as antioxidant, antithrombotic, anti-inflammatory, anti atherogenic, antiatherosclerotic, and cardioprotective effects [3235].…”
Section: Flavonoidsmentioning
confidence: 99%